Strategic match and effects of competitive strategy, market orientation and innovation strategy on hotels performance: The catalyst for economic growth of a nation - Narentheren, Kaliappen (2014)
This research investigated the causal relationship of competitive strategy, market orientation and innovation strategy on organizational performance of hotels in Malaysia. Specifically, this research considered competitive strategy (business strategy) as an independent variable, market orientation and innovation strategy (functional strategies) as mediating variables and their causal implication on performance. The theoretical framework of this study used dynamic capabilities, strategic implementation, hierarchy of organizational strategies and synthesis of the similar characteristics of each strategy. Out of a total 475 set of questionnaires which were distributed to top and middle managers of three- to five- star hotels’ in Malaysia only 114 or 24% were usable. The data were analysed through simple linear regression, multiple regression, the Sobel test and the bootstrapping test. Specifically, this research analysed the hypotheses based on a sample size of 54 for cost leadership strategy, competitor orientation and process innovation while, a sample size of 60 was used for differentiation strategy, customer orientation and service innovation. The causal relationship among competitive strategy, market orientation and innovation strategy was found significant in both sample sizes. The causal relationship among competitive strategy, market orientation and innovation strategy on organizational performance was found significant when tested with specific sample sizes of 54 and 60 but was found insignificant with a combined sample size of 114. Importantly, competitor orientation and process innovation mediated cost leadership and performance nexus, while customer orientation and service innovation mediated the differentiation and performance nexus. This study shows the specific strategic match of competitive strategy, market orientation and innovation strategy on performance. It also provides some theoretical contribution to the strategic management theory by expanding the strategy and performance nexus. Moreover, this research provides pertinent information to top and middle management to make better strategic decisions and strategy execution, especially in shaping specific competitive strategy, market orientation and innovation strategy